Bioduripave: Durian Peel Bio-Oil Innovation in Bio-Asphalt Production to Reduce Dependence on Fossil Energy - Ilma Zahra; Nabila Salsabila; Sabyla Laila Putri (Journal of Technology and Engineering, 2026)
Amid the challenges of fossil energy dependence and the environmental impacts associated with the road construction industry, bio-asphalt has emerged as a sustainable alternative. This study introduces BIODURIPAVE, a bio-oil derived from durian peel waste (Durio zibethinus) that serves as a partial substitute for bitumen in Hot Mix Asphalt (HMA). The bio-oil was produced through fast pyrolysis at temperatures ranging from 300°C to 500°C, yielding a calorific value of 24.674 MJ/kg and containing cellulose, hemicellulose, and lignin. The optimal bio-oil proportion was determined to be 5–8% of Pen 60/70 bitumen or Asbuton B 50/30. Test results indicate a reduction in CO₂ emissions of up to 20–30%, based on Life Cycle Assessment (LCA), along with enhanced oxidation resistance and improved mechanical stability (penetration value of 60–70, softening point >50°C, and Marshall stability >1000 kg). SWOT analysis identified the availability of local raw materials and opportunities for a circular economy as key strengths, while technological challenges related to pyrolysis and the absence of comprehensive regulations remain significant constraints. The implementation roadmap consists of four phases: research and development (2025), pilot implementation (2026), scalability expansion (2027), and national standardization (2028). The innovation is projected to reduce road construction costs by 12–15% per kilometer and generate 10–15 rural jobs for each production unit with a daily capacity of 5 tons. This innovation aligns with Sustainable Development Goals (SDGs) 7, 9, and 13.